Monsoon surges, tropical cyclones and extreme rainfall events in NW Madagascar - Nassor, Abdallah (Department of Oceanography, 2016)
Rainfall variability in NW Madagascar and the kinematics and thermodynamics of flood-producing weather systems affecting the region are examined. Daily rainfall in the austral summer are used to select 16 cases for the composite analysis of flood events in the period 1987-1992. In addition two cases of flood events are studied individually. The first flood event occurred in 1991 and brought420 mm of rainfall in 24 hours at Maintirano during the passage of tropical cyclone (TC) Cynthia, an eastward moving TC from the Mozambique Channel. The second flood event occurred in 1992and brought 347 mm of rainfall in 24 hours at Mahajanga due to the passage of TC Bryna, a westward moving TC from the Indian Ocean. Inter-annual rainfall variability is correlated with the indices: TC day frequency, QBO and SOI, and a useful value is found with the first index but not with the two latter global indices. An intraseasonal analysis indicates that wet spells have a duration of 15 to 20 days. Daily spectra analysisof rainfall reveals the complexity of interplay between the convective forcing features. Cycles of 10-20 days are contributed by easterly waves, while 40 day cycles are produced by monsoon surges. The composite analysis identifies the following features: an eastward shift of active convection from Mozambique across Madagascar in conjunction with a surge of the NW monsoon and weakening of the easterlies in the lower troposphere. These factors promote TC genesis. Other supporting influences include the development of an anticyclonic circulation in the upper level over the island with north westward outflow. This often coincides with an east phase QBO, an upper level eastward moving mid-latitude trough and a persistent moisture flux convergence over the island throughout TC passage. The topography of Madagascar plays an important role in the intensification of the flood producing weather system by enhancing the cloud vortex in the NW region of the island.